Health analytics : gaining the insights to transform health care - Burke, Jason, 1969- (Hoboken, New Jersey : Wiley, 2013)
"A hands-on, analytics road map for health industry leadersThe industry-wide transformation taking place across the health and life sciences ecosystem is mandating that organizations adopt new decision-making capabilities, based on science and real-world information. Analytics will be a required competency for the modern health enterprise; this book is about how to "cross the chasm." The ultimate analytics guide for the health industry leader, this essential book equips business leaders with little-to-no experience in analytics to understand how to incorporate analytics as a cornerstone of their 21st century competitive business strategy. Paints the picture for a new health enterprise, one focused on the patient Explores the financial components of this new operating model, using analytics to optimize the tradeoffs between cost and value Deals with the rising role of the consumer, using analytics to create a completely new health engagement model with individual recipients of care Looks at how analytics can drive innovations in care practice, patient-experienced medical outcomes, and analytically driven novel therapies optimized for the individual patient Presents a variety of text, tables, and graphics illustrating the various concepts being described Within each section and chapter, Health Analytics assesses the current landscape, proposing a new model/concept, sharing real-world stories of how the old and new world come together, and framing a "how-to" for the reader in terms of growing that particular set of capabilities in their own enterprises"--
What Are Customer Analytics?A Framework of Customer Analytics; Sharing Insights; Adherence; Beyond Commercial; Chapter 11: Risk Management; Risky Business; Why Are Risks So Hard?; Recharacterizing Risk Factors; The Example of Customer Segmentation; Risk Interdependencies; Everybody in the Pool; The Catch; Risk Adjustment; Borrowing from Other Industries; Growing Risks; Chapter 12: Quality and Safety; Defining Quality; Not Your Father's Toyota; On Track; Avoiding the Obvious; We Just Have to Do This; The Growing Inventory; Strategy and Performance Management; Transparency and Benchmarking.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Health services administration -- Decision making -- Mathematical models; Health facilities -- Business management; Medical care -- Information technology -- Management; Medical informatics -- Management; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Decision Making; Health Facility Administration -- methods; Health Services Administration; Medical Informatics -- organization & administration; Organizational Innovation; Health facilities -- Business management; Health services administration -- Decision making -- Mathematical models; Medical care -- Information technology -- Management; Medical informatics -- Management; Electronic books; Electronic books